THE INFLUENCE OF USING COURSE REVIEW HORAY MODEL IN TEACHING WRITING DESCRIPTIVE TEXT (A study at the Eeventh Grade of SMA Negeri 1 Pinangsori in 2020/2021 Academic Year) - DEVI SARTIKA (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract : The aimed of this study to (a) describe of using course review horay model in teaching writing descriptive text, (b) describes students’ writing descriptive text before and after using course review horay model, (c) Know whether there is any significant influence of using course review horay model at the eleventh grade of SMA Negeri 1 Pinangsori. The study was conducted at the eleventh grade of SMA Negeri 1 Pinangsori by applying experimental method (one group pretest posttest design). Sample of the study was 29 students and they were taken by using purposive sampling technique. Questionnaire and test were used in collecting data. Based on descriptive analysis, the result showed (a) the average of using course review horay model 80% (very good category) and (b) the average of students’ writing descriptive text before using course review horay model is 54.55 (bad category) and after using course review horay model is 82.10 (very good category). Furthermore, by using Wilcoxon Sign Pair Test (SPSS 22), the result showed the significant value is less than 0.05 (0.00<0.05). It means, there is any significant influence of using course review horay model in teaching writing descriptive text at the eleventh grade of SMA Negeri 1 Pinangsori in 2020/2021 Academic Year. Keywords: Course Review Horay, Model, Writing, Descriptive Text